Dirac quantization and baryon intrinsic frequencies in hypersphere soliton model - Soon-Tae Hong (Elsevier, 2021)
Quantizing a soliton on a hypersphere, we obtain the first class Hamiltonian, and evaluate the baryon physical quantities which are in good agreement with the corresponding experimental data. In particular, we find that the predicted value for axial coupling constant is comparable to its experimental value. The prediction for delta baryon mass possessing the Weyl ordering correction obtained in the first class Dirac quantization is improved comparing with that in the second class canonical quantization performed on the hypersphere. Making use of the same input parameters associated with the baryon masses, we also investigate the hypersphere soliton and standard Skyrmion models to compare the corresponding predictions for the physical quantities effectively. Next, we evaluate the intrinsic frequencies of the pulsating baryons. We thus find that the intrinsic pulsating frequency of more massive particle is greater than that of the less massive one. We explicitly evaluate the intrinsic frequencies ωN=0.87×1023sec−1 and ωΔ=1.74×1023sec−1 of the nucleon and delta baryon, respectively, to yield the identity ωΔ=2ωN.